Rotor Angle and Voltage Stability Analysis with Fault Location Identification on the IEEE 9 Bus System - Khan, H. F.; Hanif, A. H.; Anwar, N. (Engineering, Technology & Applied Science Research, 2020)
Transient stability is very imperative in multi-machine interconnected power systems in order to scrutinize and analyze the system’s performance and response. Rotor angle stability and voltage stability are studied in this paper. By applying three-phase symmetrical faults, the transient stability of the IEEE 9 bus system is studied. A characteristic double hump is analyzed in the response of the generator, which is nearer to the fault location. By analyzing the characteristic double hump, the fault location in a large interconnected power system can be determined. It is shown that, as the fault is cleared, the system takes some finite time to return to its prior state. IEEE 9 bus system is chosen as a test system, which standard parameters. MATLAB Simpower System toolbox is used for load flow and transient stability analysis.